Comparative evaluation of the pontic shield technique versus whole tooth extraction on labial crestal bone resorption using cone-beam computed tomography in the maxillary anterior region: A randomized controlled clinical trial - Mallinath Govind Jadhav; Amit Arvind Agrawal; Swapna Arunkumar Mahale; Kunal Sethi; Triveni Ashok Kale-Bachhav (Journal of Indian Society of Periodontology)
Introduction: Following tooth extraction, there is comparatively more bone loss at the buccal aspect at 3 months of healing, which may result in 56% bone loss due to resorption of the bucco-facial ridge contour. In the socket shield technique, a tooth is planned for extraction in such a way that the tooth is sectioned in two halves, a palatal section is removed and the facial part is retained. Materials and Methods: Twenty-six sites, i.e., 13 sites requiring partial tooth extraction (test sites) and 13 sites with whole tooth extraction (control sites), in the maxillary anterior region were included. In each patient, at least two sites were included (one test and one control). After both procedures, a collagen sponge was placed in the socket and sutured with silk suture. The height of the labial crestal bone and width of the socket at both sites were evaluated by the cone-beam computed tomography examination preoperatively at baseline and after a 3-month follow-up period. Results: The mean differences in labial crestal bone height and socket width from baseline to 3 month follow up were significantly lower in the test group than in the control group (P < 0.05). Conclusion: Labial crestal bone resorption was significantly less at the site where the pontic shield technique (PST) was used than at the site with whole tooth extraction. The reduction in socket width (bucco-lingually) was also significantly less at the site where the PST was used compared to whole tooth extraction sites.